Canaans calamitie, Ierusalems misery, and Englands mirror. The dolefull destruction of faire Ierusalem by Titus, the sonne of Vespasian Emperour of Rome, in the yeare of Christs incarnation 74. Wherein is shewed the wonderfull miseries which God brought upon that citty for sinne, being utterly ouerthrowne and destroyed by sword, pestilence, and famine. Briefly gathered into this small volume, for the benefit of all well disposed persons, wherein they shall find many strange and notable things, worthy to be regarded and had in remembrance. [electronic resource] : (1625)
Summary goes here